Ageing response of an Al-Mg-Mn-Sc-Zr alloy processed by laser metal deposition in thin-wall structures. (December 2018) - Zhao, Tong; Cai, Wangcan; Dahmen, Marius; Schaible, Jonathan; Hong, Chen; Gasser, Andres; Weisheit, Andreas; Biermann, Tim; Kelbassa, Ingomar; Zhang, Han; Gu, Dongdong; Schleifenbaum, Johannes Henrich
Abstract: The use of aluminium alloys containing Sc and Zr in additive manufacturing (AM) provides new solutions for lightweight design. Representative thin-wall structured parts were additively fabricated with a commercially available Al-4.55Mg-0.51Mn-0.65Sc-0.30Zr alloy in Laser Metal Deposition (LMD) process. A bi-directional and a uni-directional scan strategy were applied and laser power from 500 W to 600 W was used. Nanohardness tests were conducted on specimens aged at 300 °C for up to 19 h to observe the ageing responses. Fine-grained microstructures with few micro-sized precipitates containing Sc- and Zr were found in the last track of every specimen. The area formed by the track-overlapping was the opposite, but an apparent hardening was observed only after the ageing. AM-processes with local remelting are facing the challenge to exert the potential strengthening effect of aluminium alloys containing Sc. The mushy state must be suppressed to prevent the waste of the expensive rare elements. Graphical abstract: Highlights: Laser metal deposition of AlMgMnScZr-alloy. Comprehensive hardness testing to study the ageing response and thermal history. Relationship between hardening, precipitation and grain refinement.